Diseño de un centro polideportivo vertical con enfoque de integración, sostenibilidad y salud para el fortalecimiento deportivo en el sector de Pilanquí en Ibarra - Muñoz Buitrón, Israel Vicente (2024)
In response to current limitations in sports infrastructure in Pilanquí, Ibarra, this project proposes the design of a vertical sports complex emphasizing community integration, urban sustainability, and health promotion. Through a thorough analysis of the local environment and sports needs, significant issues such as inadequate facilities, insecurity, and prevalent sedentary lifestyles among residents were identi fied. The architectural proposal aims not only to address these infrastructure deficiencies but also to strengthen the connection between public space and the sports complex, providing a secure and adaptable environment for a variety of sports and community activities. It is expected that this project will contrib ute not only to the physical well-being of Pilanquí residents but also to the social and environmentally sustainable development of the community.